Analysis of 155 cases of head and neck cancers seen over a 3-year period at University of Port Harcourt Teaching Hospital - O.G. Omitola; B.B. Osagbemiro; C.C. Obiorah (Nigerian Dental Association, 2014)
Objective: Head and neck cancers are group of malignancies that affect the head and neck region. They remain a serious public health concern worldwide with more than half a million cases diagnosed annually. The prevalence and presentation vary from one region to the other. The purpose of this study is to determine the pattern of presentation of this lesion in the University of Port Harcourt Teaching Hospital (UPTH). Method: Records of all histologically diagnosed head and neck cancers during the study period were retrieved from the Cancer Registry of UPTH. Information collected were age, sex, histopathological diagnosis and site of primary lesion. The data were analyzed with SPSS version 20 and summary statistics of frequency and central tendency were presented. Result: There were 155 patients comprising 95 (61.3%) males and 60 (38.7%) females, giving a male to female ratio of 1.6:1. The age range of the patients was 1-85 years with a mean age of 37.8±20.6. The highest incidence of HNC was found in the 40-49 (18.7%) age group while least number of patients was found in the 80-89 (2.6%) age group. Carcinomas (44.5%) was the most common malignant lesion with squamous cell carcinoma been the most common. The next most common lesions were the Lymphomas (25.8%). The neck (29.7%) was the most  commonly affected site followed by the oral cavity (22.5%) while the parotid region and the larynx with 1.9% respectively were the least affected sites. Conclusion: Squamous cell carcinomas were the most frequent HNC seen in our centre and the patients within the 5th decade were most frequently affected with male predominance. Common sites affected were the neck, oral cavity, eye, and the nasopharynx.